What measure of inflation should a central bank target? - N. Gregory Mankiw; Ricardo Reis (European Central Bank (ECB), 2002)
This paper assumes that a central bank commits itself to maintaining an inflation target and then asks what measure of the inflation rate the central bank should use if it wants to maximize economic stability. The paper first formalizes this problem and examines its microeconomic foundations. It then shows how the weight of a sector in the stability price index depends on the sector's characteristics, including size, cyclical sensitivity, sluggishness of price adjustment, and magnitude of sectoral shocks. When a numerical illustration of the problem is calibrated to U.S. data, one tentative conclusion is that the central bank should use a price index that gives substantial weight to the level of nominal wages.
Keywords: E42; E52; E58; 330; inflation targeting; monetary policy